Barriers and Facilitators of Fruit and Vegetable Consumption in Renal Transplant Recipients, Family Members and Healthcare Professionals—A Focus Group Study - Boslooper-Meulenbelt, Karin (Nutrients, 2019)
Low fruit and vegetable consumption is associated with poor outcomes after renal transplantation. Insufficient fruit and vegetable consumption is reported in the majority of renal transplant recipients (RTR). The aim of this study was to identify barriers and facilitators of fruit and vegetable consumption after renal transplantation and explore if certain barriers and facilitators were transplant-related. After purposive sampling, RTR (n = 19), their family members (n = 15) and healthcare professionals (n = 5) from a Dutch transplant center participated in seven focus group discussions (three each for RTR and family members, one with healthcare professionals). Transcripts were analyzed using social cognitive theory as conceptual framework and content analysis was used for identification of themes. Transplant-related barriers and facilitators were described separately. In categorizing barriers and facilitators, four transplant-related themes were identified: transition in diet (accompanied by, e.g., fear or difficulties with new routine), physical health (e.g., recovery of uremic symptoms), medication (e.g., cravings by prednisolone) and competing priorities after transplantation (e.g., social participation activities). Among the generic personal and environmental barriers and facilitators, food literacy and social support were most relevant. In conclusion, transplant-related and generic barriers and facilitators were identified for fruit and vegetable consumption in RTR. The barriers that accompany the dietary transition after renal transplantation may contribute to the generally poorer fruit and vegetable consumption of RTR. These findings can be used for the development of additional nutritional counseling strategies in renal transplant care.